PROGRAM PENGEMBANGAN DESA MITRA (PPDM) TAHUN KE-2: MEWUJUDKAN KAMPUNG BAMBU ALU SEBAGAI SENTRA EKOWISATA DI TENGAH PANDEMI COVID-19 - Muhammad Rizky Prawira; Sitti Hadijah; Ritabulan Ritabulan; Nuraeni M (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Kampung Bambu Alu, is a program for developing a tourist destination, bamboo center and sustainable ecotourism site in Alu Village. The village is located in Alu District, Polewali Mandar Regency, West Sulawesi. This program has been running since last year and involving 3 main partners, namely, the Alu Local Government, Cahaya Uwai Manurung Craftsmen Group and the Alu Youth Community Forum (Forum Komunitas Pemuda Alu). However, there are still a number of problems encountered by partners and Alu people, from the decrease of income and productivity due to the pandemi to the lack of use of e-marketing. All these problems may potentially jeopardize the sustainability of this bamboo and ecotourism business in the future. For that, PPDM team from Universitas Sulawesi Barat through the Partner Village Development Program (PPDM) Year 2 has carried out a series of follow-up activities for realizing an Ecotourism Village “Kampung Bambu Alu”. Some activities that have been carried out including the socialization of PPDM Year 2 with the Covid-19 Socialization, Workshop on Ecotourism and Bamboo Products, IT and E-Commerce Workshop, adding the production equipment for bamboo products, making murals for photo spots, and publications for both journals and mass media. All these activities has posed some impacts on the economic and social aspects of Alu people. These include increasing the demands for Alu bamboo products, increasing the income of the community, increasing the quality and quantity of the products produced by Alu bamboo craftsmen, and increasing the public awareness in implementing the health protocols.